(untitled) (Biodiversitas Journal of Biological Diversity, 2021)
Abstract. Rehman A, Saeed S, Ahmed A. 2021. Genetic diversity and population structure of Seriphidium Sub-genus of Artemisia from different terrains of Balochistan, Pakistan. Biodiversitas 22: 2658-2664. Seriphidium is one of the largest sub-genus of Artemisia growing in different geographical populations and terrains of Balochistan Pakistan. This genus is economically important and used as folk medicine. The genus is highly variable, besides morphological characterization, molecular authentication is also needed for novel drug discovery. Three significant species of the genus viz., S. quettense, S. oliverianum, and S. maritimum were selected for morphological and molecular characterization and phytochemical investigation. Genetic variability assessment was carried out by polymorphic bands analysis by using molecular markers in 18 accessions collected from two sites, namely, Ziarat and Hazarganji-Chiltan National Park, Balochistan, Pakistan. A combined molecular marker system by using 17 Randomly Amplified Polymorphic DNA (RAPD) and 9 Inter-Simple Sequence Repeats (ISSR) amplified 231 loci, of which 111 were polymorphic (48% polymorphism). Phenolic contents and Flavonoids were estimated for phytochemical assessment. Results revealed that the highest phenolic compounds were in S. quettense when compared with other investigated taxa. In conclusion, molecular marker profiling together with phytochemical variation of all three species exhibited genetic diversity and chemical variation. The findings of the current investigation can further be used as a baseline study for the implementation of conservation strategies. In addition, phytochemical assessment can be utilized for modern drug discovery